Networked filtering with Markov transmission delays and packet disordering - Liu, Andong (2018)
This is concerned with the filtering problem for a class of networked systems with Markov transmission delays and packet disordering. The transmission delays are considered to be a Markov chain with finite states, and a packet reordering mechanism is proposed to deal with the packet disordering. According to the original transition probability matrix of Markov delays, a new method is developed to calculate the reordered transition probability matrix. A sufficient condition is derived such that the filtering error system is exponentially stable in the mean-square sense. Moreover, an optimal filter is designed by solving a convex optimisation problem. An illustrative example is provided to show the effectiveness of the proposed filtering method.